Successful therapeutic strategy for a patient with obese end-stage kidney disease by simultaneous laparoscopic sleeve gastrectomy and implantation of a buried peritoneal dialysis catheter: A case report - Yamashita, Tomohisa; Sato, Tatsuya; Yamamoto, Kazuyuki; Abiko, Atsuko; Nishizawa, Keitaro; Matsuda, Masahiro; Ebihara, Yuma; Maehana, Takeshi; Tanaka, Toshiaki; Yano, Toshiyuki; Kobayashi, Hironori (Frontiers in Medicine, 2022)
For morbidly obese patients with end-stage kidney disease (ESKD), there are often difficulties in accessing, implementing, and maintaining kidney replacement therapy. Although recent weight-loss surgery has the potential to solve these problems, its therapeutic strategy and appropriate perioperative management for morbidly obese patients with ESKD have not been established. Here, we describe the case history of a 47-year-old man diagnosed with ESKD due to obesity-related glomerulopathy with an uncorrected estimated glomerular filtration rate (eGFR) of 16.1 ml/min. He hoped for kidney transplantation but was not eligible due to his high body mass index (36.9 kg/m2). Therefore, a combination strategy for both attaining weight loss and preparing for kidney replacement therapy was needed. We performed modified laparoscopic sleeve gastrectomy (LSG) combined with a buried catheter for peritoneal dialysis (PD), which resulted in reduction of multiple surgical invasions while simultaneously preparing for PD. After these operations, his body mass dropped to below 30.0 kg/m2, making him a candidate for kidney transplantation, while maintaining PD. Finally, he was able to have kidney transplantation with success. Collectively, in this case, our novel therapeutic approach was able to avoid multiple surgeries, to assist catheter insertion by laparoscopy, and to provide optimal kidney replacement therapy for an obese patient with ESKD. Simultaneous LSG and implantation of a buried PD catheter may be a promising strategy for morbidly obese patients with ESKD.